(untitled) (World Science, 2023)
Aim of the research was to study improvement of the results of surgical treatment of duodenal ulcer bleeding based on the use of endovascular embolization. Gastrointestinal bleeding is a relatively common condition with a wide range of underlying causes. In most cases, this acute bleeding is effectively managed by conservative, medical or endoscopic procedures. However, the proportion of endoscopically unrecognized or controlled non-variceal gastrointestinal bleeding still requires alternative, sometimes surgical, treatment. The current S2k guideline Gastrointestinal Bleeding gives importance to interventional radiology in considering its minimally invasive endovascular interdisciplinary therapy options, guideline-oriented endovascular treatment of Gastrointestinal bleeding by embolization and implantation of covered stents is a treatment approach with good technical and clinical success rates and low complication rates. Gastrointestinal bleedings (GIBs) are pathological conditions associated with significant morbidity and mortality. Embolization without angiographic evidence of contrast media extravasation is proposed as an effective procedure in patients with clinical and/or laboratory signs of bleeding. The purpose of this systematic review is to define common clinical practice and clinical and technical outcomes of blind and preventive embolization for upper and lower gastrointestinal bleeding. Knowledge of vascular anatomy is essential to achieve adequate hemostasis. Endovascular embolization dramatically reduces the mortality rate in high-risk patients who require open surgery after failed endoscopy, further studies are needed to fully address these objectives.